Written Historical Sources on shipbuilding and the archaeological study of a post-medieval Mediterranean shipwreck: the Gagliana grossa case study - Bondioli, Mauro; Nicolardi, Mariangela (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
During the excavation campaigns conducted on the Gnalić shipwreck dated to the late 16th century, problems pertaining to the documentation, interpretation and graphic representation of the hull’s structural elements were addressed. A project was launched with the aim of finding a solution that combines archaeological data with iconography, archival documents and written sources about shipbuilding. Using 3D graphic technologies, the idea was to sketch the probable shape of the entire hull and update it as the excavations proceed. Archaeologists should always be able to monitor the progress made in the study of the ship in this way.